Analysis of the problem of meaning in the sciences in a phenomenological perspective - José Manuel Chillón Lorenzo (Sociología y Tecnociencia, 2018)
The sciences do not all have them. When they do not, they end up extending their pattern of rationality to all dimensions of life that are not measured or calculated. Phenomenology warns that, torn from the common trunk of philosophy, the sciences leave us fasts to know what truly interests man. And this is what Husserl calls meaning. The emerging anthropology in the s. XX is a good example of how meaningless, this science turns man into an object, in a fact, affected as all, by the principle of causality.